Optimization of the Temperature Stability of Fluxgate Sensors for Space Applications - Topal, Ugur; Svec, Peter; Can, Hava; Celik, Fatmanur; Birlikseven, Cengiz; Skorvanek, Ivan; Andrejka, Frantisek (IEEE-Inst Electrical Electronics Engineers Inc, 2021)
Fluxgate magnetometers are widely used in many places for the measurement of weak magnetic field, but are sensitive to variations of sensor temperature. Therefore, their stabilization against temperature variation is required especially for outdoor applications. In this work, temperature dependencies of fluxgate sensors having the cores of one homemade, one commercially obtained finemet alloy, and a commercially obtained supermalloy alloy in ribbon form were examined. It was observed that the heat treatments of the studied cores affect the sensitivity of the sensors in different ways. For instance, while the scale factor of the sensor with the core from in-house prepared finemet ribbon increased from 1.19 MV/T to 3.12 MV/T, the scale factor of the sensor with the supermalloy core increases by 20 times in magnitude (41.6 kV/T to 0.92 MV/T) after heat treatment. Our analysis performed in the temperature interval from -50 degrees C to +85 degrees C reveals that temperature dependencies of the sensors also show differences depending on the core material. In addition to differences seen on the temperature dependence of the studied cores, the most stable one was the sensor with the heat treated in-house prepared finemet core. The variation of the scale factor in the 135 degrees C temperature range was 9.8 %. However, by analyzing the temperature dependences of the scale factors we could decrease the error coming from temperature variations to less than 1.0 % in magnitude of the output signal due to the observed linear dependence between the scale factor and the temperature of this sensor.
Keywords: Aerospace applications; finemet; fluxgate magnetometer; magnetic field measurement; magnetic sensors; soft magnetic materials; supermalloy